1996
DOI: 10.1007/bf02738704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TRH and TRH-like peptide pGLU-HIS-GLY-NH2 on adrenocortical cell proliferation in rats

Abstract: The effects of three peptides-colon mitosis inhibitor (CMI), its amide, and thyroliberin (TRH)-on the adrenocortical cell proliferation were studied. As an index of cell proliferation, the incorporation of bromodeoxyuridine (BrDU) into adrenocortical cell nuclei was used. It was found that: Twelve hours after the injection, only CMI-amide significantly increased the total number of BrDU-immunopositive cell nuclei per equatorial section of the adrenal cortex. This mitogenic effect was observed separately for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Relatively high doses of TRH (1 ng/ml) are unable to stimulate DNA synthesis or even to slightly decrease (10 ng/ml TRH) the number of BrdU-labeled cells, although no statistical difference has been noted (P= 0.094). Previous studies have shown that TRH and/or TRH-like peptides can directly or indirectly stimulate the proliferation of thymus cells, anterior pituitary cells, and adrenocortical cells (Pawlikowski and Slowinska-Klencka 1994;Pawlikowski et al 1992;Zerek-Mełeń 1996). Recently, TRH has been found potentially to maintain and stimulate thyrotroph abundance in aggregate cell cultures of postnatal rat pituitary gland (Pals et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Relatively high doses of TRH (1 ng/ml) are unable to stimulate DNA synthesis or even to slightly decrease (10 ng/ml TRH) the number of BrdU-labeled cells, although no statistical difference has been noted (P= 0.094). Previous studies have shown that TRH and/or TRH-like peptides can directly or indirectly stimulate the proliferation of thymus cells, anterior pituitary cells, and adrenocortical cells (Pawlikowski and Slowinska-Klencka 1994;Pawlikowski et al 1992;Zerek-Mełeń 1996). Recently, TRH has been found potentially to maintain and stimulate thyrotroph abundance in aggregate cell cultures of postnatal rat pituitary gland (Pals et al 2006).…”
Section: Discussionmentioning
confidence: 95%